P118 Post discharge pulmonary rehabilitation for acute exacerbation COPD does not always reduce re-admission rates. (14th November 2013) - Roberts, SE; Kodumooru, N; Purcell, S; Williamson, A; Broomfield, H; Restrick, LJ; Stern, M
Abstract : Introduction: Post-discharge pulmonary rehabilitation (PR) within 7–10 days after discharge from hospital admission for acute exacerbation of COPD (AECOPD) has been shown not only to result in the well-described benefits of PR (reduced breathlessness, improved exercise performance and health-related quality of life), but also to reduce emergency department attendances over a 3 month period. We report the outcomes of a locally-provided post-exacerbation PR (PEPR) pilot study for patients admitted to hospital with AECOPD, and compares outcomes and subsequent 90-day re-admission rates with published RCT data showing re-admission reduction from 33 to 7% 1 . Methods: Patients were recruited during AECOPD admission to start PR within 10 days of discharge from hospital. Taxi transport was offered to all patients.Outcome measures chosen were change in: 6-Minute Walking Test (6MWT), Hospital Anxiety and Depression Score (HADS), Chronic Respiratory Disease Questionnaire (CRDQ), and 90-day re-admission rates. Results: 43 patients were offered PEPR, 32 started and 21/32 (66% of starters, 49% of all referrals) completed the course (>11/16 sessions). Mean (range) age was 67(40–86) years and mean (SD) %predicted FEV1 32(15)%. Median time (range) between discharge from hospital and starting PEPR was 8(0–17) days. There were clinically significant improvements in 6MWT median (range) 27%(-40- + 233) and CRDQ dyspnoea domain 0.79(-0.60– + 3.00). There was no clear effect on 90-day re-admission rate: 45% patients who started PEPR were re-admitted v 58% who were offered but declined PEPR. Local 90-day re-admission rate for all 2012 AECOPD admissions was 39%. Conclusion: This study failedto replicate published reductions in re-admission rates in a patient population that was more severe than the comparison study, mean%predicted FEV1 32% v 52% 1 . Value of PEPR programmes in reducing AECOPD re-admission rates needs further investigation across disease severity spectrum. An additional area that would benefit from further investigation is completion rate for PEPR 2 ; completion rate from referral for PEPR at 49% compares to 43% for our standard PR programme. References: Seymour et al . Outpatient pulmonary rehabilitation following acute exacerbations of COPD. Thorax 2010;65:423–428 National Institute of Health Research, HTA no 13/24 'does starting PR early following AECOPD improve adherence and outcomes compared to starting rehabilitation later?'